Employing color hints In the ad Commercial (Journal of the College of Basic Education, 2026)
Commercial prints are achievements for a profitable purpose by influencing the recipient's perception and motivating him to take a behavior in order to be influenced by them. A group of contrasting and compatible colors are employed with connotations that express its content and message. They achieve rhythm and movement in order to attract attention and direct the eye in the design space. Thus, the research consists of four chapters. The first chapter included the research problem, which was a question: How to employ color connotations in commercial advertisements? In order to achieve the desired results through an objective determined by the researcher as: (Studying the expressive connotations of colors for printed advertising. And setting a set of instructions on how to benefit from and use colors in commercial advertisements) and in order to pursue the research objective, the axes included in the second chapter were determined (the first topic included color, employing color connotations in the advertising achievement) As for the second topic (the possibility of employing color in printed design), according to the theoretical framework, indicators were extracted, and the research procedures were determined in the third chapter based on the descriptive analytical approach for the research community, which amounted to (30) thirty commercial advertisements for the year 2023, an advertisement from Al-Hafez Company for Electrical Appliances. (3) advertisements were chosen intentionally as a research sample, and the results were reached and discussed in the fourth chapter. Among the most important results achieved by the researcher during her study of the research: (Color connotations carry a set of meanings and interpretations that affect the recipient to read the advertisement. Employing color connotations in a thoughtful manner by the designer contributes to strengthening the idea of ​​the commercial advertisement between the recipient and the commodity (advertised) It also included a set of conclusions and recommendations.